A taxonomic revision of Stenoglottis (Orchideae, Orchidoideae, Orchidaceae) - Phillips, Dean P.; Bytebier, Benny (Phytotaxa, 2020)
Based on a published morphological and phylogenetic analysis, species delimitation in Stenoglottis is here revised, and five species (six taxa) are now recognized: S. fimbriata (with two varieties), S. longifolia, S. inandensis, S. woodii, and S. macloughlinii. Stenoglottis fimbriata subsp. saxicola and S. zambesiaca are synonymised here with S. fimbriata, S. modesta is reduced in rank to S. fimbriata var. modesta and S. molweniensis is synonymised with S. longifolia. The three spurred species, S. inandensis, S. woodii and S. macloughlinii, are retained. We include revised descriptions, diagnoses and a morphological key, in which characteristics of the floral spurs, labella, leaves, bracts, and auricles contribute most clearly to distinguishing the taxa. Distributions maps and photos showing important diagnostic characters and morphological variation are also presented.